Iconclass (2005)
[Dt.:] "Iconclass" ist ein ikonographisches Klassifikationssystem, das von Henri van de Waal entwickelt wurde. Die Website informiert über das Projekt und bietet gebührenpflichtige CD-ROM-Lizenzen, Downloads und Updates. Zudem existieren Testzugänge ('experimental' web browsers) in verschiedenen Sprachen. - [Engl.:] "Iconclass" is a subject specific international classification system for iconographic research and the documentation of images, developed by Henri van de Waal. The website informs about the project and offers chargeable CD-ROM licences, downloads and updates. Besides there are 'experimental' web browsers in different languages.